Review of the species of the genus Ochthera from China (Diptera: Ephydridae) - Zhang, Junhua; Yang, Ding (Zootaxa, 2006)
The Chinese species of the genus Ochthera Latreille are reviewed. Two species, Ochthera japonica Clausen and O. macrothrix Clausen, are recorded from China for the first time. Two species, O. guangdongensis sp. nov. and O. hainanensis sp. nov., are described as new. A key to the species from China is given. The distribution of the genus in China is discussed.